Creating innovation infrastructure of the Russian Federation on the basis of SPP - A. N. Rodionov (Путеводитель предпринимателя)
Creation of innovation infrastructure in Russia is becoming a mandatory requirement for the country’s development. Structural, financial and legislative approaches form the basis of successful implementation of the State innovation policy. Foreign experience without understanding modern Russian reality will not give a positive effect. Using the PPP mechanism opens up opportunities for attracting investment in innovative infrastructure.